The Mechanisms of Sevoflurane-Induced Neuroinflammation - Huang, Xiangfei; Ying, Jun; Yang, Danying; Fang, Pu; Wang, Xifeng; Zhou, Bin; Zhang, Lieliang; Fang, Yang; Yu, Wen; Liu, Xing; Zhen, Qingcui; Hua, Fuzhou (Frontiers in Aging Neuroscience, 2021)
Sevoflurane is one of the most commonly used inhaled anesthetics due to its low blood gas coefficient, fast onset, low airway irritation, and aromatic smell. However, recent studies have reported that sevoflurane exposure may have deleterious effects on cognitive function. Although neuroinflammation was most widely mentioned among the established mechanisms of sevoflurane-induced cognitive dysfunction, its upstream mechanisms have yet to be illustrated. Thus, we reviewed the relevant literature and discussed the most mentioned mechanisms, including the modulation of the microglial function, blood–brain barrier (BBB) breakdown, changes in gut microbiota, and ease of cholinergic neurotransmission to help us understand the properties of sevoflurane, providing us new perspectives for the prevention of sevoflurane-induced cognitive impairment.